Implementasi Direct Marketing pada Bank BPR Datagita Mustika - Dedi Junaedi; Wahida Mardhatillah; Evinovita Evinovita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyze the implementation, barriers and direct marketing solutions at PT. BPR Datagita Mustika. The method used is descriptive qualitative analysis with an interview approach and a saturated sample survey. The results showed that there were five media for direct marketing activities that were actively carried out by BPR Datagita Mustika, namely catalog media, online channels such as Instagram and Whatsapp, kiosk/office marketing, telemarketing, and face-to-face sales/offers, while the less active was direct post marketing ( direct mail). Marketing through television and online marketing on website and social media has not been done. BPR Datagita Mustika can defend itself and develop because it is able to capture and process business and social phenomena around it. Furthermore, the company has efforts in the field of marketing, namely marketing communications that are more focused on direct marketing elements. Barriers faced by BPR Datagita Mustika related to the implementation of direct marketing on the face-to-face sales dimension, namely the lack of employee skills so that they must be given training and motivation, catalog marketing is constrained by high costs so that an electronic catalog needs to be made to be more efficient and effective. Telemarketing marketing is constrained by an unstable network so that it is more careful in choosing and adapting to the development of e-business technology.